FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Thun 2013-2015) - Novit, Febrina Lourentya; , Fauzan, S.E., M.Si., Ak (2016)
Audit Delay is the length of time measured from the completion of the audit the closing date of the financial year until the date of completion of an independent audit report (Wiwik Utami, 2006:4). The purpose of this research is to examine the signification impact of firm size, operation loss and profit, profitability, solvability, auditor's opinion and reputation of public accountant toward audit delay. In this research, the type of used data is quantitative data with a population of 69 companies listed in the Indonesia Stock Exchange in 2013-2015. The method of analysis used to test the hypothesis is multiple linear regression analysis with the study sample was 23 companies were selected based on purposive sampling method during the third period. Based on the results of the analysis can be concluded that firm size have no significant effect on audit delay, operation loss and profit have no significant effect on audit delay, profitability have no significant effect on audit delay, solvability have no significant effect on audit delay, auditor's opinion have no significant effect on audit delay and reputation of public accountant have significant effect on audit delay.